Blockbuster de science-fiction : étendue, extension, morcellement du territoire - Gaspard Delon (ReS Futurae)
Since the late 1970s, Hollywood science fiction blockbusters have been an attractive but random investment. Although the genre is well represented at the top of the box office, it is not a guarantee of success. It regularly records serious setbacks and is deployed in a heterogeneous range of productions. The market share of science fiction cinema within North American production (difficult to assess because of the overlap between SF cinema, horror, disaster films or superhero films) is limited but significant and expanding, sometimes spectacularly, in the 2000s. The increasingly systematic recourse to franchises tends to marginalize unitary projects and pushes for the constitution of extended fictional ensembles closely controlled by the majors, which engage in harsh competition in this field, aiming, at the very least, to consolidate their positions. In this relatively stable landscape, now dominated by Disney, the emergence of new content producers and the development of television series appear to be powerful factors of imbalance.